1988
DOI: 10.1073/pnas.85.12.4553
|View full text |Cite
|
Sign up to set email alerts
|

Beta 2-adrenergic mechanisms in experimental arthritis.

Abstract: We have studied (i) the contribution of specific adrenergic receptors to the proinflammatory effects of the sympathetic nervous system in experimental arthritis and (it) the phases of the disease during which the sympathetic nervous system influences joint injury. Severity of joint injury was measured radiographically 28 days after induction of adjuvant arthritis in control rats and in rats treated with a variety of sympatholytic agents at various times during the course of the disease. Rats treated with a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(71 citation statements)
references
References 24 publications
4
66
1
Order By: Relevance
“…Second, we were unable to identify a particular nerve quality required for K/BxN serum-transferred arthritis. This finding contrasts with previous reports of an effect of manipulating the SNS in other mouse models of inflammatory arthritis (sometimes via the same inhibitors) (3,15). A likely explanation for the divergent results is that the models previously interrogated are rather different: Unlike the K/BxN serum-transfer system, they encompass both the initiation and effector stages of arthritis and depend on the injection of an adjuvant to induce disease.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Second, we were unable to identify a particular nerve quality required for K/BxN serum-transferred arthritis. This finding contrasts with previous reports of an effect of manipulating the SNS in other mouse models of inflammatory arthritis (sometimes via the same inhibitors) (3,15). A likely explanation for the divergent results is that the models previously interrogated are rather different: Unlike the K/BxN serum-transfer system, they encompass both the initiation and effector stages of arthritis and depend on the injection of an adjuvant to induce disease.…”
Section: Discussioncontrasting
confidence: 55%
“…For example, neuroendocrine hormones have well-known anti-inflammatory activities, first documented for corticosteroids in the arthritis context (2). Subsequently, motor neurons, the sympathetic nervous system (SNS), the parasympathetic nervous system (PNS), and sensory fibers have all been documented to modulate inflammation (3)(4)(5).…”
mentioning
confidence: 99%
“…The effects of treatment with drugs that interact with α-AR on disease pathology are dependent on time of treatment relative to disease course [365]. Treating rats with α-or α 2 -antagonists from adjuvant challenge through severe disease increases disease severity [363,365,366]. However, it α-, α 1 -or α 2 -AR antagonist treatment begins at disease onset, disease pathology is significantly ameliorated ( [365,366] Lorton and Lubahn, unpublished observations).…”
Section: Sympathetic Regulation Of Autoimmune Diseasesmentioning
confidence: 99%
“…Additionally, sympathetic nerves in the inflamed joint interact with substance P-containing nerves that convey pain and modulate local immune responses. Levine et al [363] using an adjuvant-induced arthritis (AA) model in Sprague-Dawley rats has shown that chronic administration of the β-AR blocker, propranolol, attenuates the severity of joint injury. In contrast, selective denervation of the lymph nodes that drain the hind limbs (the popliteal and inguinal) prior to immunization to induce experimental arthritis exacerbates the disease [364].…”
Section: Sympathetic Regulation Of Autoimmune Diseasesmentioning
confidence: 99%
“…β2-ARs have been shown to have a role in the time-dependent, immunomodulating effect of the SNS (22)(23)(24) and they are expressed on innate and adaptive immune cells of humans and rodents (7). Peripheral blood mononuclear cells (PBMCs), specifically monocytes, B cells and CD8 + T cells, from RA patients express lower levels of β2-ARs compared with healthy subjects (25) and the receptor density on RA synovial fluid lymphocytes is even less (26).…”
Section: β2-adrenergic Receptor Expression and Function In Rheumatoidmentioning
confidence: 99%